Laying Ground for Automated Manhole Inspection – a Review - Jorge, Filipe (2020)
Artigo de livro: Sustainability and Automation in Smart Constructions Proceedings of the International Conference on Automation Innovation in Construction (CIAC-2019), Leiria, Portugal